Focused targeting of inhaled magnetic aerosols in reconstructed in vitro airway models. (30th March 2021) - Ostrovski, Yan; Dorfman, Semion; Poh, Wilson; Chye Joachim Loo, Say; Sznitman, Josué
Abstract: The pulmonary tract is an attractive route for topical treatments of lung diseases. Yet, our ability to confine the deposition of inhalation aerosols to specific lung regions, or local airways, remains still widely beyond reach. It has been hypothesized that by coupling magnetic particles to inhaled therapeutics the ability to locally target airway sites can be substantially improved. Although the underlying principle has shown promise in seminal in vivo animal experiments as well as in vitro and in silico studies, its practical implementation has come short of delivering efficient localized airway targeting. Here, we demonstrate in an in vitro proof-of-concept an inhalation framework to leverage magnetically-loaded aerosols for airway targeting in the presence of an external magnetic field. By coupling the delivery of a short pulsed bolus of sub-micron ( 500 nm diameter) droplet aerosols with a custom ventilation machine that tracks the volume of air inhaled past the bolus, focused targeting can be maximized during a breath hold maneuver. Specifically, we visualize the motion of the pulsed SPION-laden (superparamagnetic iron oxide nanoparticles) aerosol bolus and quantify under microscopy ensuing deposition patterns in reconstructed 3D airway models. Our aerosol inhalation platform allows for the first time to deposit inhaled particles to specific airway sites while minimizing undesired deposition across the remaining airspace, in an effort to significantly augment the targeting efficiency (i.e. deposition ratio between targeted and untargeted regions). Such inhalation strategy may pave the way for improved treatment outcomes, including reducing side effects in chemotherapy.